Designing equitable telehealth solutions for outpatient surgical care in a safety-net population: a human-centered design approach - Lara Z. Chehab; Diyah Mettupalli; Jenny R. Cevallos; Camille Rogine; Amanda Sammann; Sandhya Kumar (BMC Health Services Research)
Abstract Background The SARS CoV-2 (COVID-19) pandemic catalyzed a dramatic shift in healthcare delivery, with telemedicine emerging as a common mode of care provision. While pre-pandemic telemedicine services were more commonly used for preventive visits and had better adherence among younger and more affluent demographics, the landscape of telehealth in the post-pandemic period has shifted significantly to include surgical visits and publicly-insured patient populations. Without specific insights from patients and clinicians to guide this transition, telehealth delivery risks exacerbating disparities in access, experience and outcomes for medically underserved populations. Methods We utilized a human-centered design (HCD) approach to gain insights into patient and clinician perspectives on telehealth delivery at a surgical outpatient clinic in an urban safety-net hospital and level 1 trauma center. During the Inspiration phase of HCD, we conducted 19 in-depth interviews with patients and surgical clinicians, and applied a combined thematic analysis and design synthesis approach to identify key insight statements representing actionable tensions across cohorts. During the Ideation phase of HCD, we held a structured brainstorming session to identify solutions and facilitated a discussion with surgical faculty to co-design and refine a prototype. Results Interview analysis revealed 12 main themes, which were then reorganized into 5 core insights across both groups: “In-person appointments can be resource intensive for patients, making their attendance costly in more ways than one”; “When sacrificing connection for convenience, telehealth exacerbates discrimination felt by historically marginalized patients”; “Personal interactions are crucial for establishing new relationships and repairing mistrust between patients and clinicians”; “Visual cues and non-verbal communication are essential for personalized and effective surgical care”; “Patients and clinicians value the human infrastructure built into the in-person visit experience.” Brainstorming participants generated ideas from the first insight statement. Subsequent prototyping and co-design sessions led to the development of a screening prototype allowing both clinic staff and patients to book telehealth appropriate appointments. Conclusions This study offers a HCD approach to developing insights and tailoring health service interventions to the local contexts for safety-net providers. By understanding the unique needs and preferences of underserved populations, we can develop telehealth interventions that increase adoption and ensure equitable access to care.